2004
DOI: 10.1016/j.ejcts.2003.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord cells for cardiovascular tissue engineering: a comparative study

Abstract: Tissue engineering of cardiovascular constructs by using UCA, UCV and UCC is feasible in an in vitro environment. Cell growth, morphology, characteristics and tissue formation were comparable between UCA, UCV, UCC and VC. UCC represent an attractive, readily available autologous cell source for cardiovascular tissue engineering offering the additional benefits of utilizing juvenile cells and avoiding the invasive harvesting of intact vascular structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 17 publications
4
52
1
Order By: Relevance
“…UCM cells demonstrate excellent cell growth properties on bioabsorbable polymer constructs (75). UCM cells were used to seed blood vessel conduits fashioned from rapidly bioabsorbable polymers and grown in vitro in a pulse duplicator bioreactor (76).…”
Section: Ucm Cells For Tissue Engineeringmentioning
confidence: 99%
“…UCM cells demonstrate excellent cell growth properties on bioabsorbable polymer constructs (75). UCM cells were used to seed blood vessel conduits fashioned from rapidly bioabsorbable polymers and grown in vitro in a pulse duplicator bioreactor (76).…”
Section: Ucm Cells For Tissue Engineeringmentioning
confidence: 99%
“…Thus, Naughton et al [33] and Purchio et al [34] derived "prechondrocytes," from explant cultures of UC WJ, and Mitchell et al [35], using a similar approach, reported that the fibroblast-like cells of WJ could be induced to differentiate into "neural-like" cells expressing neuron-specific enolase (NSE), as well as other neural cell markers. Romanov et al [36], using a different approach, enzymatically digested mesenchymal precursor cells from the UC vasculature endothelial surface, and Kadner et al [37,38] minced either UC vessels or whole cord to derive an autologous cell source of myofibroblasts for cardiovascular tissue engineering. Chacko and Reynolds [39] described the cells residing in WJ as "smooth muscle cells," but Takechi et al [40] refined the description to "myofibroblasts" after in situ labeling of vimentin, desmin, α-actin, and myosin, which has been recently confirmed by Kadner et al [38].…”
Section: Introductionmentioning
confidence: 99%
“…Although hUC-MSCs have exhibited a therapeutic effect in DMD/BMD, MSCs derived from different tissue sources have not been uniformly effective in clinical practice (23). MSCs derived from the umbilical cord have a significant advantage over those derived from bone marrow, placenta, or other tissues, as hUC-MSCs are easy to acquire and culture, and the cells have a high proliferation rate (32) and low immunogenicity (33).…”
Section: Discussionmentioning
confidence: 99%
“…Cells isolated from the umbilical cord tissue have also been shown to be more effective in rescuing photoreceptors and visual function, and to be capable of sustained population doublings without karyotypic changes, thus proving useful in retinal diseases (21). Cultured mesenchymal stem cells (MSCs) from the human umbilical cord artery (UCA), umbilical cord vein (UCV), whole umbilical cord (UCC) and saphenous vein segments have exhibited a myofibroblast-like morphology and mechanical function in vitro (23). The cells are abundant, easy to harvest and to culture and have lower immunogenicity.…”
Section: Introductionmentioning
confidence: 99%